COLOSS survey: global impact of COVID-19 on bee research. Issue 5 (19th October 2020) - Dall'Olio, Raffaele; Blacquiere, Tjeerd; Bouga, Maria; Brodschneider, Robert; Carreck, Norman L.; Chantawannakul, Panuwan; Dietemann, Vincent; Kristiansen, Lotta Fabricius; Gajda, Anna; Gregorc, Ales; Ozkirim, Aslı; Pirk, Christian; et al.
Abstract : The socio-economic impacts of COVID-19 on society have yet to be truly revealed; there is no doubt that the pandemic has severely affected the daily lives of most of humanity. It is to be expected that the research activities of scientists could be impacted to varying degrees, but no data exist on how COVID-19 has affected research specifically. Here, we show that the still ongoing COVID-19 pandemic has already diversely and negatively affected bee research at a global level. An online survey disseminated through the global COLOSS honey bee research association showed that every participant ( n  = 230 from 56 countries) reported an impact on one or more of their activities. Activities that require travelling or the physical presence of people (meetings and conferences, teaching and extension) were affected the most, but also laboratory and field activities, daily operations, supervision and other activities were affected to varying degrees. Since the basic activities are very similar for many research fields, it appears as if our findings for bee research can be extrapolated to other fields. In the light of our data, we recommend that stakeholders such as governments and funding bodies who support research should facilitate the wide implementation of web-based information technology required for efficient online communication for research and education, as well as adequately loosened restriction measures with respect to field and laboratory work. Finally, increased flexibility in administration and extension of research grants and fellowships seem to be needed. It is apparent that adequate responses by all stakeholders are required to limit the impact of COVID-19 and future pandemics on bee science and other research fields.